Karakteristik Ibu dan Bayi Berat Lahir Rendah (BBLR) di RSU Sundari Medan Tahun 2012 - Fathia Amanda; Rasmaliah ,MKes; Taufik Ashar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Infants with Low Birth Weight (LBW) are infants which borned with a birth weight under 2500 grams. According to WHO estimated, more than 20 million infants in the world (15,5% from newborn infants in the world) every years borned with LBW and influenced about 16% LBW in developing countries. Datas of General Hospital Sundari Medan in 2012, there are 188 cases of LBW (8,6%) from 2170 birth. To know the characteristics of mothers and infants with LBW in General Hospital Sundari Medan in 2012,it is conducted a descriptive research by case series design.Population and sample totaled as 188 people.Data’s been analyzed by using Chi-Square test, t-independent and Anova test. From the results, it was obtained that proportion of mothers with LBW infants based on sociodemographic, medical risk factors and patient records aged 20-35 years 79,8%, Islam 84%, housewives 54,3%, first pregnancy 52,7%, gestational age 37-42 weeks 54,8%, spacing pregnancy < 2 years 55,1%, hemoglobin concentration ≥11 gr% 35,6%, good pregnancy history 67%, no complication of pregnancy 66%, patient comes itself 88,3%. Proportion of infants with LBW based on 1500-<2500 grams 76,6%, no complication of LBW 85,6% . Mothers treatment on average 2,3 days, infants treatment of average 2,4 days, mothers circumstances when to go home healthy 83%, infants circumstances when to go home healthy 50,5%. There is no significant differences between spacing pregnancy (p= 0,614),hemoglobin concentration (p= 0,399), infants treatment of average based on complication of LBW (p= 0,878), mothers treatment on average based on circumstances when to go home (p= 0,377), infants treatment of average based on circumstances when to go home (p = 0,421). There is significant differences between mothers aged based on classification of LBW (X2= 9,873; p=0,007), parity based on classification of LBW (X2= 10,009; p= 0,002), gestational age based on classification of LBW (X2= 10,033; p=0,007), pregnancy history based on classification of LBW (X2= 14,770; p=0,000). The hospital is expected to complete the recording of status card especially hemoglobin concentration as well as the recording of antenatal care to know preganancy history. The hospital must increase quality of life for the infants and for the health department to give an information of nutrient for pregnancy women and ideal spacing pregnancy. Keywords : Low Birth Weight, The characteristics of mothers, The characteristics of infants